Endoplasmic reticulum chaperones inhibit the production of amyloid-β peptides - Hoshino, Tatsuya (Portland Press Ltd., 2007)
Aβ (amyloid-β peptides) generated by proteolysis of APP (β-amyloid precursor protein), play an important role in the pathogenesis of AD (Alzheimer's disease). ER (endoplasmic reticulum) chaperones, such as GRP78 (glucose-regulated protein 78), make a major contribution to protein quality control in the ER. In the present study, we examined the effect of overexpression of various ER chaperones on the production of Aβ in cultured cells, which produce a mutant type of APP (APPsw). Overexpression of GRP78 or inhibition of its basal expression, decreased and increased respectively the level of Aβ40 and Aβ42 in conditioned medium. Co-expression of GRP78's co-chaperones ERdj3 or ERdj4 stimulated this inhibitory effect of GRP78. In the case of the other ER chaperones, overexpression of some (150 kDa oxygen-regulated protein and calnexin) but not others (GRP94 and calreticulin) suppressed the production of Aβ. These results indicate that certain ER chaperones are effective suppressors of Aβ production and that non-toxic inducers of ER chaperones may be therapeutically beneficial for AD treatment. GRP78 was co-immunoprecipitated with APP and overexpression of GRP78 inhibited the maturation of APP, suggesting that GRP78 binds directly to APP and inhibits its maturation, resulting in suppression of the proteolysis of APP. On the other hand, overproduction of APPsw or addition of synthetic Aβ42 caused up-regulation of the mRNA of various ER chaperones in cells. Furthermore, in the cortex and hippocampus of transgenic mice expressing APPsw, the mRNA of some ER chaperones was up-regulated in comparison with wild-type mice. We consider that this up-regulation is a cellular protective response against Aβ.